“Philosophy Needs To Find A Place For Imagination Also In The Analysis Of Action”: Faculty Interview with Professor Katja Vogt - Basaran, Ayda (Columbia Undergraduate Research Journal, 2017)
In her recent project, Imagination and Agency, Professor Vogt addresses the gap between the philosophical theory and empirical research. I was curious about how this project aims to incorporate philosophical questions into an interdisciplinary debate. She explains that there is a significant body of empirical work on mental simulation and imagination as components of agency, since philosophers have also long been interested in imagination. However, philosophers tend to focus on what are called “lofty domains”: thought experiments, science, and art. Vogt argues that philosophy needs to find a place for imagination also in the context of the analysis of action. She thinks that it’s a long-standing idea that, when you make a decision, you decide between options that you consider possible. This is why her project examines the modal scope, the study of ways in which propositions can be true or false, of agential thought, since decision making is concerned with what is and what is not possible. As an example, she cites Aristotle, , who argued that no one deliberates about whether to become a god, because it’s impossible to become a god.